INFLUENCE OF POLYMERIZATION FACTORS AND VARYING SHADE COMPOSITIONS OF BULK FILL RESIN-BASED NANOHYBRID COMPOSITES ON UNDER-SURFACE TEMPERATURE - HARAHAP, SEFTY ARYANI; YUDHIT, ASTRID; HARAHAP, NASPATI; CANDRA, GRACIELLA (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to evaluate the influence of polymerization factors and varying shade compositions of bulk-fill resin-based nanohybrid composites on under-surface temperature. Methods: A total of 120 bulk-fill resin-based nanohybrid composite specimens (n=10) consisting of IVW (whiter), IVB (medium), and IVA (darker) shades were inserted in one bulk into a polyvinyl siloxane mold with a diameter of 5 mm and a thickness of 4 mm, divided into 2 subgroups of irradiation times (20 s and 30 s) and 2 subgroups of light curing sources (LED and QTH). When the specimen was polymerized, the under-surface temperature was measured with a K-type digital thermocouple. Data analyzed using Three-Way ANOVA and Tukey HSD Post Hoc tests. Results: It showed significantly different QTHs that generated lower under-surface temperature than LEDs (P<0.05); whiter shade generated the highest temperature among all. However, there was no significant difference between 20 s and 30 s irradiation time (P>0.05). Conclusion: It was concluded that the under-surface temperature generated by polymerization factors and varying shade compositions of bulk fill resin-based nanohybrid composites in this study was still acceptable and safe for dental pulp tissue.